GE_GERICHTE P/18678/2009 vom 18. April 2013 - GE Cour de justice (2013)
; CLASSEMENT DE LA PROCÉDURE ; VOIES DE FAIT ; INJURE ; LÉSION CORPORELLE ; ACTE D'ORDRE SEXUEL ; CAS BÉNIN | CPP.319; CP.52; CP.126; CP.123; CP.177; CP.191